Distribution and Growth Patterns of the Tambakan Fish (Helostoma temminckii) and the Climbing Perch (Anabas testudineus) in the Musi River, Rantau Bayur Subdistrict, Banyuasin - Indah Anggraini Yusanti; Hilda Zulkifli; Indra Yustian; Arif Wibowo (Universitas Muhammadiyah Palembang, 2025)
ABSTRACT The Musi River in Rantau Bayur District, Banyuasin Regency, is an important habitat for kissing gourami (Helostoma temminckii) and climbing perch (Anabas testudineus). This study aimed to analyze the distribution, sex ratio, growth patterns, condition factor, and the relationships of both species with water environmental characteristics. The study was conducted from September to November 2025 at five stations representing different levels of anthropogenic pressure. Environmental parameters measured included temperature, pH, salinity, dissolved oxygen, water transparency, total dissolved solids, and sediment. The results showed that the populations of both species were dominated by females. Climbing perch were generally found in medium size classes, while kissing gourami were dominated by small-sized individuals. The growth pattern of climbing perch was negative allometric, whereas kissing gourami showed a shift from positive to negative allometric growth. The condition factor of climbing perch remained relatively stable, while that of kissing gourami increased toward the end of the observation period. Water characteristics were dominated by silt–clay substrates with high organic matter content, indicating moderate pollution levels. Correspondence analysis revealed relationships between fish size classes and physico-chemical water parameters. Overall, the Musi River still supports the presence of both species, although environmental pressures may influence their population structure.